Applications of Nanotechnology in Cement and Concrete Science - Barbhuiya, Salim; Qureshi, M. (IGI Publishers, 2014)
The properties of concrete are strongly influenced by the properties of its components and hydrates at the nanoscale. Therefore, application of nanotechnology in cement and concrete science will engender new opportunities for improvement of strength and durability of concrete. The objective of this chapter is to advance the science and engineering of nanotechnology in modifying and monitoring the behaviour and performance of cement and concrete at the nanoscale. The chapter assists in the identification of promising new research and innovations in concrete materials using nanotechnology that can result in improved mechanical properties, volume change properties, durability, and sustainability. The chapter also provides a unique base for scientists, engineers, and practitioners to help set the future direction of the use of nanotechnology in cement and concrete science.